Treatment of Genital Warts by 30% Salicylic Acid Peel and Cautery Vs 5% Imiquimod Cream and Cautery in Shahid Jabar Dermatology and Venereology Center - Mohammed, Lana; Elethawi, Ali Mozn Dhahir (Journal of Sulaimani Medical College, 2025)
Background: Genital warts are the epidermal manifestation of human papillomavirus infection, associated with physical discomfort and psychosocial distress. Our study aimed to compare the efficacy and safety between two combinations: Group A: 30% salicylic acid peel with cautery (SA peel + CA) Group B: 5% Imiquimod cream with cautery (IMQ+CA). Methods: 70 patients were recruited in a single-center, open label, and parallel-group randomized clinical trial. Participants were randomly assigned to one of the treatment arm, assessments conducted at baseline and every two weeks for 12 weeks. Results: 30% (SA + CA) obtained significantly and more rapid and consistent clearance rate. The clearance rate was markedly higher in the SA peel arm across all time points, reaching 94.3% by week 10, while the IMQ cream arm only reached 54.3% by week 12. Additionally, recurrence rates were significantly lower in the SA peel group (8.6%) than in the IMQ cream group (48.6%) (P < 0.001). In terms of side effects, the SA peel group reported milder and less frequent adverse events (25.7%), whereas the IMQ cream group experienced moderate to severe side effects in 77.1% of cases (p < 0.001). Conclusion: Both treatments were effective, but 30% (SA peel +CA) demonstrated higher efficacy, faster clearance, lower recurrence rate, fewer and milder side effects, higher patient satisfaction, and greater quality of life improvement; therefore, this combination represents a promising, effective, and well-tolerated treatment option for genital warts
Keywords: genital warts; salicylic acid; imiquimod; cautery; human papillomavirus (HPV)